Information Systems: Methods, Models, and Applications 4th International United Information Systems Conference, UNISCON 2012, Yalta, Ukraine, June 1-3, 2012, Revised Selected Papers - Mayr, Heinrich C.; Kop, Christian; Liddle, Stephen; Ginige, Athula; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This volume constitutes the proceedings of the 4th International United Information Systems Conference, UNISCON 2012, which was held in Yalta, Ukraine, during June 1-3, 2012. UNISCON 2012 was affiliated with the 8th International Conference on ICT in Education, Research, and Industrial Applications, ICTERI 2012. The 14 full papers, four short papers, and three extended abstracts presented with a keynote speech were carefully reviewed and selected from 96 submissions. The topical sections covered are: data management; applications; modeling and semantics; and social issues in information systems.
Business Process Management: A Holistic Management Approach -- Maintaining Desirable Properties of Information by Inconsistency-Tolerant Integrity Management -- Heuristics-Based Workload Analysis for Relational DBMSs -- Information Technology for the Decision-Making Process in an Investment Company -- Long-Term Forecasting Technology of Macroeconomic Systems Development: Regional Aspect -- Using Lightweight Activity Diagrams for Modeling and Generation of Web Information Systems -- Towards Conceptualizing Quality-Related Stakeholder Interactions in Software Development -- Agent-Based Implementation for the Discovery of Structural Difference in OWL-DL Ontologies -- Cognitive Modeling and Support for Ambient Assistance -- Architecture for Social Life Network to Empower People at the Middle of the Pyramid -- Towards Quality Monitoring and Evaluation Methodology: Higher Education Case-Study -- Validating OntoElect Methodology in Refining ICTERI Scope Ontology -- Composition-Nominative Logics in Rigorous Development of Software Systems -- Adaptable Enterprise Information Systems Development Using Advanced Active Data Dictionary Framework -- The Model for Enhanced Variability Management Process in Software Product Line -- Providing the Interactive Studying of the Students Which Is Controlled by Distance with Web-Portal E-olimp -- A Template-Based Method to Create Efficient and Customizable Object-Relational Transformation Components -- Are Anti-goals Needed in Systems Design? -- Model and Tools for Multi-dimensional Approach to Requirements Behavior Analysis -- A Layered Architecture Approach for Large-Scale Data Warehouse Systems -- Towards Medical Screening Information Technology: The Healthgrid-Based Approach -- Knowledge-Oriented Approach to Requirements Engineering in Ambient-Assisted Living Domain.
Keywords: Computer science; Software engineering; Information storage and retrieval systems; Management information systems; Computer Science; Information Systems Applications (incl. Internet).; Business Information Systems; Information Storage and Retrieval; Software Engineering